The Effect of the JIRE Collaborative Learning Model Based on Phylearn Media on Students Learning Outcomes in the Topic of Heat and Temperature in School - Ilato, Nursuciani Radja; Ntobuo, Nova Elysia; Setiawan, Dewa Gede Eka; Samatowa, Lukman; Mohamad, Wahyu Muzizat; Yunus, Muhammad (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Collaborative learning has the potential to address these challenges by promoting problem-solving through collective participation within groups. This research investigates the effect of the Jire Collaborative Learning model integrated with Phylearn media on students’ learning outcomes regarding heat and temperature. The study was motivated by low student achievement, primarily attributed to conventional teaching methods to engage students in active participation. This quasi-experimental research employed a one-group pre-test-post-test design involving 25 seventh-grade students at SMP Negeri 4 Monano. The Jire Collaborative model emphasizes active student collaboration, while Phylearn provides interactive multimedia support to help visualize abstract scientific concepts. The findings reveal a significant improvement in students’ cognitive performance (levels C2-C4) after the intervention, indicating that the integrated approach effectively improves conceptual understanding. This influence is demonstrated by the difference in students’ learning outcomes before and after applying the JIRE model, where the average pre-test score of 46.4 increased to 81.05 in the post-test. The t-test results indicate that this difference is statistically significant, with a significance value of 2.10, less than 0.05. These findings confirm a significant difference between students’ pre-test and post-test scores after applying the JIRE collaborative learning model, indicating that this model effectively improves students’ learning outcomes. These results suggest that technology-supported collaborative learning is a promising strategy for improving the quality of science education at the junior high school level.